THE IMPACT OF GOOGLE CLASSROOM AND EXTENSION ON STUDENT’S MOTIVATION AND ENGAGEMENT IN EFL CLASSROOM (THE CASE STUDY OF SMA ISLAM ATHIRAH BONE) - Mohd Tahir, Asman Bin; -, Suharyadi; Tresnadewi, Sintha (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
In today's technology-driven world, students are increasingly surrounded by digital tools, with easy access to vast amounts of information (Egbert, 2009). From a pedagogical perspective, integrating technology into education is essential for successful learning outcomes (Sebring and Chicago School Consortium, 2013). Despite this, less than half of students utilize technology for academic purposes, though 92% have access to it at home. The evolving information age has made previously expensive technologies accessible to many (Edwards, 2009), necessitating that educators adapt to this technological integration. This study examines the impact of Google Classroom and its extensions on student motivation and engagement in English as a Foreign Language (EFL) classrooms at SMA Islam Athirah Bone. The research highlights the importance of incorporating real-world technology into EFL classes to enhance student interest and motivation (Usher & Center on Education, 2012). Technology supports diverse learning styles, fosters community, and provides hands-on experiences, especially beneficial for students with learning disabilities (Heafner, 2004; Liu, 2016). As English is a global language, its learning is critical for accessing research and higher education (Morris & Maxey, 2014). Traditional methods have evolved, with technology playing a pivotal role in English language instruction (Graddol, 2012).This qualitative study uses video recordings, interviews, and observation checklists to explore the impact of technology on student engagement and motivation in EFL classrooms. Data collection involved classroom observations and semi-structured interviews with teachers and students. The findings indicate that both teachers and students at SMA Islam Athirah Bone perceive the use of Google Classroom and its extensions as beneficial for active learning and engagement. This study contributes to a deeper understanding of how technological tools can enhance EFL learning experiences and suggests practical applications for better classroom interactions.